Radar absorbing properties of different size carbon nanotube reinforced polymer composites - Yilmaz Atay, Gül; Bilgiç, Nurşah (Frontiers in Materials, 2024)
Carbon nanotubes (CNTs), which have a diameter on the nanometer scale, are tube-like materials composed of carbon and graphite sheets. Carbon nanotubes play an important role in many fields such as nanotechnology, electronics, optics and material science due to their superior properties such as high elasticity, high thermal conductivity, low density and being more chemically inert. In this study, the use of carbon nanotubes in radar absorbing materials (RAM) to reduce the reflection of electromagnetic waves was investigated. In this sense, by using a polymeric composite structure reinforced with carbon nanotubes, a material with unique properties such as solid absorption, low weight/thickness and cost-effectiveness has been produced, minimizing the reflection of electromagnetic waves. For this purpose, carbon nanotubes with different particle sizes of 8 nm, 30-50 nm and 48-78 nm were blended with polyester at the ratio of 1%. The resulting composites were characterized using a Network analyzer in the frequency range of 8 to 12 GHz. According to the results obtained, it was observed that radar absorption increased with increasing particle size. It has been determined that by changing the particle sizes of carbon nanotubes in composites, the absorption bands can be adjusted to suit different applications in different frequency bands.